Guidelines for seismic design of flexible buswork between substation equipment. - Dastous,Jean-Bernard
During an earthquake, flexible buswork between interconnected equipment is stretched and compressed dynamically. This causes additional forces to be transmitted to the equipment. Design guidelines for flexible buswork have been determined through non-linear finite element simulations on models of typical installations. For a proper design, the required amount of slack in the buswork is established using an estimation of the maximum horizontal relative displacement between equipment in a pair, with an additional length function of the buswork shape and its corresponding stiffness. To avoid multi-connected equipment effects, all pairs of equipment within a given electrical phase must be designed in such way. Of utmost importance, equipment must be designed with an additional static load at its attachment point, to take account of the unavoidable forces transmitted by the buswork. From the previous criteria, a methodology for the design of universal flexible buswork has been established for use within Hydro-Quebec and shown to be a simple way to cover most pairs of equipment within a given voltage level and for a given seismic demand. This methodology resulted in design tables specifying the required conductor length of possible shapes, for different distances between equipment. The guidelines described in this paper are proposed for possible adoption by other utilities.
Keywords: Earthquakes; Flexible buswork; Interaction; Interconnection; Stranded conductor; Substation design